Genetic location of the gene (ush) specifying periplasmic uridine 5'-diphosphate glucose hydrolase (5'-nucleotidase) in Escherichia coli K-12. - Beacham, I R (1976)
Further genetic mapping to two- and three-factor crosses show that the ush gene is closely linked to two other genes hemG and pisA, and that the probable gene order is proC-hemG-plsA-ush-gal.